Unmanned Aerial Vehicle Robot untuk Pemadam Api dengan Rancangan Alat Pemadam yang Efisien - Farouq, Ardiansyah Al; Riansyah, Moch Iskandar; Habibi, Ahmad (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
When firefighters extinguish a fire there are certain points that are difficult to pass, while the speed of extinguishing the fire is important. Therefore, the existence of a UAV (Unmanned Aerial Vehicle) that can easily reach the area is very important to help the firefighters. Then the extinguisher used to extinguish must also be specially designed because the ability to carry the robot's UAV (Unmanned Aerial Vehicle) is limited. The flying robot UAV (Unmanned Aerial Vehicle) design used is a multicopter robot. Multicopter which is designed to have 6 propellers. Specially designed extinguisher is also designed to be able to extinguish the fire efficiently with the designed multicopter. The extinguisher is designed in the form of an inverted umbrella with the fabric of the umbrella using a fire extinguisher or a fire-resistant cloth. With this system design, the robot UAV is very efficient to use to extinguish fire in the form of a multicopter. The extinguisher designed has succeeded 100% in extinguishing the fire with an average time of 5 seconds, while when using water the fire is extinguished in an average time of 37.5 seconds.Â Keywords : UAV, Robot, Fire fighting,Mmulticopter, Extinguisher.AbstrakPada saat petugas pemadam api melakukan pemadaman apiÂ  terdapat beberapa titik tertentu yang sulit dilalui, sedangkan kecepatan dalam pemadaman adalah yang penting. Oleh sebab itu adanya UAV (Unmanned Aerial Vehicle) yang dapat dengan mudah menjangkau daerah tersebut sangatlah penting untuk membantu para pemadam. Kemudian alat pemadam yang digunakan untuk memadamkan juga harus dirancang khusus karena kemampuan angkut UAV (Unmanned Aerial Vehicle) robot terbatas. Desain UAV (Unmanned Aerial Vehicle) robot terbang yang digunakan adalah berbentuk multicopter robot. Multicopter yang didesain memiliki 6 baling-baling. Kemudan alat pemadam yang dirancang juga dirancang khusus agar dapat memadamkan api dengan efisien dengan multicopter yang telah didesain. Alat pemadam yang dirancang berupa payung terbalik yang bagian kaiin payung menggunakan kain pemadam atau kain tahan api yang biasa digunakan untuk memadamkan api. Dengan desain sistem tersebut maka UAV robot sangat efisien digunakan untuk memadamkan api dalam bentuk multicopter. Alat pemadam yang dirancang telah berhasil 100% memadamkan api dengan rata-rata waktu 5 detik, sedangkan bila menggunakan air maka api padam dalam waktu rata-rata 37.5 detik.Kata Kunci : UAV, Robot, Pemadam kebakaran, Multicopter, Alat pemadam.